2015
DOI: 10.1136/archdischild-2015-309056
|View full text |Cite
|
Sign up to set email alerts
|

Supporting decisions to increase the safe discharge of children with febrile illness from the emergency department: a systematic review and meta-analysis

Abstract: The use of clinical prediction models can improve discrimination between serious and self-limiting infections in children. The application of low-risk thresholds may help to rule out serious infections and discharge children from the ED without empirical antibiotics. A growing evidence base for prediction rules has so far failed to translate into validated rules to aid decision-making. Future work should evaluate decision rules in well designed impact studies, focusing on the need for hospital admission and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…value for children with recent onset fever (6-9). These biomarkers have been combined with clinical data in risk prediction models to identify patients at risk of SBIs (2,6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). However, while a number of studies have suggested various cut-offs for CRP to evaluate the risk of SBIs and IBIs, only one study proposed an updated procalcitonin cut-off in its risk prediction model (10).…”
Section: Key Notesmentioning
confidence: 99%
“…value for children with recent onset fever (6-9). These biomarkers have been combined with clinical data in risk prediction models to identify patients at risk of SBIs (2,6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). However, while a number of studies have suggested various cut-offs for CRP to evaluate the risk of SBIs and IBIs, only one study proposed an updated procalcitonin cut-off in its risk prediction model (10).…”
Section: Key Notesmentioning
confidence: 99%
“…If this is achieved, it would avoid unnecessary hospitalisation and medical interventions. A recent systematic review summarised the published studies using clinical prediction rules with specific emphasis on how they could be used to support the safe discharge of children from the ED 9. To complement the available tools, an evidence-based clinical algorithm integrating point-of-care diagnostic tests, could aid the admission and discharge decision-making process for children with low-risk infections and significantly reduced attendance times 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…11 Supporting clinicians in ruling out SBIs may reduce unnecessary hospital admissions in children. 12 A number of studies have reported the diagnostic accuracy of clinical 13 and laboratory 14 variables in febrile children. More recently, risk prediction models that combine clinical variables have been evaluated, 2, 15 and in one, the addition of the C-reactive protein (CRP) improved diagnostic accuracy.…”
mentioning
confidence: 99%